Regulating Tumorigenicity and Cancer Metastasis through TRKA Signaling - Fan, Yichao; Zhang, Boya; Du, Xinhui; Wang, Bangmin; Yan, Qiang; Guo, Liangyu; Yao, Weitao (Current Cancer Drug Targets, 2024)
Tropomyosin receptor kinase (TRK) A, TRKA, is a specific binding receptor of nerve growth factor (NGF), which plays an essential role in the occurrence and progression of human cancers. TRKA overexpression has been proven to be a powerful carcinogenic driver and has been verified in many tumors. The TRKA receptor kinase domain is over-activated in an NGF-dependent manner, accompanied by activation of downstream signal pathways, such as RAS-MAPK, PI3K-AKT, JAK2-STAT3 pathway, PLC γ pathway, and Hippo pathway, which participate in tumor cell proliferation, invasion, epithelial-mesenchymal transition (EMT), perineural invasion (PNI), drug resistance, and cancer pain. In addition, chimeric oncogenes produced by the fusion of NTRK1 and other genes are also the direct cause of tumorigenesis and cancer development. The newly developed TRK inhibitors can improve symptoms and tumor regression in cancer patients with overexpression of TRKA or NTRK1 fusion gene. With the emergence of drug resistance, next generation of TRK inhibitors can still maintain strong clinical efficacy in the case of TRK kinase domain mutations, and these inhibitors are in clinical trials. This review summarizes the characteristics and research progress of TRKA, focusing on the regulatory role of the TRKA signal pathway in different tumors. In addition, we have summarized the clinical significance of TRKA and the TRK inhibitors. This review may provide a new reference for the study of the mechanism of TRKA in different tumors, and also provide a new perspective for the in-depth understanding of the role of TRKA as a biomarker and therapeutic target in human cancer.
Keywords: TRKA fusion